The Influence of Brand Experience, Perceived Value, Brand Preference, and Customer Satisfaction on Repurchase Intention at Mixue Beverage Stores in Indonesia - Carolin; Margaretha Pink Berlianto (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
This study examines the influence of brand experience, perceived value, brand preference, and customer satisfaction on repurchase intentions within the competitive landscape of the international beverage market, focusing on Mixue's operations in Indonesia. Amidst the challenges of globalization, where emotional and psy-chological customer responses significantly affect purchasing de-cisions and brand loyalty, this research aims to delineate the fac-tors critical to consumer retention strategies. Utilizing a quantita-tive approach, data were collected from 163 respondents in the Greater Jakarta area, all of whom had recent transactions with Mixue. The analysis, conducted using the Partial Least Square Structural Equation Model (PLS-SEM), demonstrates that brand experience, perceived value, brand preference, and customer sat-isfaction each significantly enhance repurchase intentions. These findings underscore the importance of sensory and emotional en-gagement in improving brand perception and satisfaction, which are pivotal in driving customer loyalty and repeat business. Con-sequently, the study suggests that beverage companies should fo-cus on optimizing these elements through strategic sensory brand-ing and reasonable pricing to bolster brand preference and sus-tain growth in a highly competitive environment.